TATA KELOLA ADMINISTRASI DESA DALAM PENYELENGGARAAN PEMERINTAHAN DI ERA OTONOMI DESA (STUDI DI DESA BUO KECAMATAN LOLODA KABUPATEN HALMAHERA BARAT) - Mais, Trisno; Rumapea, Patar; Rares, Joyce (Sam Ratulangi University, 2015)
Abstract: This research in order to acquire a thesis making a Bachelor degree Holders in theFaculty of social and Political Science Unsrat Manado. Moving on from the pre study done by researchers,that turns into alleged 1980 Village Administration Governance has not been applied in accordance withPERMENDAGRI NO. 32 in 2006 about the village Administration Guidelines. This is because there aresome administration village of 1980 which have not been applied. Thus, the researchers saw a need to reviewand note the application of Administrative Governance at the village of 1980. This research uses qualitativeresearch methods. The data collected from the stages of observation, in-depth interviews and documentation.On the collection of data on completed by using the guidelines of the interview, in which there are 9informants interviewed. The informant is the ninth of which start from the head of Loloda (1) and (8) thevillage government. After being interviewed, the researchers analyzed the results of the interviews throughseveral stages. Among the first with the collection of data is done through observation or interviews and thendo record keeping and typing and editing as necessary, both the reduction of the holding against existingdata selection, data analysis, summarize the sharpen as well as discard data that is not required, the thirdprovides data and simplifying data have been obtained in order to facilitate research in the conclusion, thefourth withdrawal With drawl , verify their conclusions with a review the records or data acquired andanalyzed as a result including brainstorm with friends colleagues and then take the conclusion. The resultsshowed that the Administration's Governance is still not applied optimally as expected by PERMENDAGRINO. 32 in 2006. The conclusion that can be drawn from the results of this research is that found there areseveral administration which has not been applied. Data book including the land of the village, the village'sland book, appointment book, book, book the population mutation data recap of the population end of themonth, BPD, book appointment book expedition BPD. So it is inferred that sub District and villageGovernments must still work together to realize the village administration governance better.Keyword: application of Administrative Governance,